Pigmentos a base de Cobalto para aplicação em revestimentos cerâmicos - Costa, Asenete Frutuoso da (2014)
Ceramic pigments that own mainly the spinel structure AB2O4 are becoming a matter of great scientific and technological interest due to the ability of accommodate different cations in its structure, allowing different dopings and thus obtaining different colors. Studies on ceramic pigments currently are being directed to the development of stable and pigments obtained at low temperatures and with greater reproducibility. This work aims at the use of inorganic pigments for applications in ceramic tiles, investigating the influence of doping and calcination temperature on the coloring pigments and ceramic glazes. the based pigments of CoCr2O4, CoAl2O4, Co0,8Zn0,2Cr2O4 and Co0,8Zn0,2Al2O4 were synthesized by a chemical route using commercial gelatin as organic precursor. The materials were characterized by thermogravimetric analysis (TG), X-ray diffraction (XRD), infrared spectroscopy (FTIR) spectroscopy scanning electron microscopy (SEM) in the UVVisible region and colorimetry. The results confirmed the feasibility of synthesis used, the route presented pigments crystal structures and the desired phases were obtained from 500 °C with increased crystallinity and the crystallite size. The pigments have hues ranging from green to violet according to their doping and calcination temperatures.